Safety and efficacy of a feed additive consisting of a tincture derived from roots of Gentiana lutea L. (gentian tincture) for use in all animal species (FEFANA asbl). (21st April 2021) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of a tincture from the roots of Gentiana lutea L. (gentian tincture) when used as a sensory feed additive for all animal species. The product is a ■■■■■ solution, with a dry matter content of approximately 4.3%. The product contains on average 0.0836% polyphenols (of which 0.0463% are flavonoids and 0.0027% xanthones) and 0.0022% gentiopicroside. The FEEDAP Panel concludes that gentian tincture is safe at the maximum proposed use level of 50 mg/kg complete feed for short‐living animals (animals for fattening). The FEEDAP Panel considers that the use in water for drinking is safe provided that the total daily intake of the additive does not exceed the daily amount that is considered safe when consumed via feed. Considering the genotoxic potential of gentiopicroside and xanthones (gentisin and isogentisin), no conclusions can be drawn for long‐living animals (companion animals, horses and animals for reproduction). No safety concern would arise for the consumer from the use of gentian tincture up to the highest safe level in animal nutrition. In the absence of data, no conclusions can be drawn on the potential of the tincture to be a dermal/eye irritant or a skin sensitiser. The data available do not allow to conclude on risks of genotoxicity and carcinogenicity for dermal exposure. Use of the tincture derived from G. lutea as a flavour in animal feed is not expected to pose a risk for the environment. Since G. lutea and gentian root extract are recognised to flavour food and their function in feed would be essentially the same as that in food, no further demonstration of efficacy is considered necessary for the tincture under application.